Validity and Reliability Analysis of the Body Image After Breast Cancer Questionnaire in the Turkish Population - Adalı Aker, Derya; Namal, Esat (Cerrahpaşa Medical Journal, 2023)
Objective: To evaluate the perception of body image in female patients with breast cancer using the Turkish version of the Body Image After Breast Cancer Questionnaire (tBIBCQ), to test its validity-reliability, and to determine the psychiatric features of patients. Methods: The study group consisted of 80 patients aged 18 - 75 years with breast cancer. The control group comprised 80 patients of the same age with no history of cancer who were visiting an internal medicine specialist. A sociodemographic data form, the tBIBCQ, Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) were used as tools. Results: The Cronbach alpha value for tBIBCQ was 0.761. The Spearman-Brown correlation coefficient (SBCC) was found as 0.609. Eight factors for type 1 and 7 factors for type 2 described 73.4% and 70.2% of the total variance, respectively. The mean scores of Vulnerability (V), Body Stigma (BS), Limitations (L), Body Concerns (BC), Transparency (T) and BAI subscales were higher in the study group. A positive correlation was found separately between the BAI and BDI with each BIBCQ subscale. BS, L, AC (Arm Concerns), BAI, BDI variables were higher in those who underwent surgery. Higher scores were obtained in patients with mastectomy compared with patients with lumpectomy in terms of BS, BC, AC and BDI. Conclusion: The tBIBCQ form is reliable and valid for detecting the effect of breast cancer on the body image of Turkish women. Cite this article as: Adalı Aker D, Namal E. Validity and reliability analysis of the body image after breast cancer questionnaire in the Turkish population. Cerrahpaşa Med J. 2023;47(3):296-301.